Development from the Periphery Village-Owned Enterprises, Women's Empowerment, and Information Technology. - Rohim Rohim; Imam Sunarto; Muhamad Lutvi (Program Pascasarjana Universitas Negeri Makassar, 2023)
One of the Indonesian government's programs is building from the periphery. This study aims to find out development from the periphery or village through the management of village-owned enterprises (BUMDes), women's empowerment, and the use of information technology. This study uses a descriptive qualitative research method, with in-depth interviews with several key informants. The informant determination technique uses a purposive technique. Data analysis went through the stages of condensation, description and explanation, then finally interpretation. The results of the research are: first, village development through BUMDES. Second, empowering women by involving women in the structural management of BUMDES, and as MSME owners. Third, the use of social media as a promotion from the BUMDES business unit. In short, BUMDES is able to empower women and use information technology to improve rural development